Line extension influence on brand image: a study on the alcoholic beverage market in Brazil - Cabanes, Sébastien (2014)
The present study has the objective of understanding the influence of line extensions on the image of vodka brands. The research was performed by organizing various focus groups with vodka consumers in São Paulo. These focus groups allowed exploring and analyzing how the last line extensions of vodka brands have modified the image the consumers had of the brand. Three hypotheses were distinguished as an outcome of the research: (1) The influence of a line extension on brand image depends heavily on the initial image the consumers have of the brand. For a vodka brand with an average or bad image, launching a line extension with a perceived average or bad quality does not modify the brand image. On the contrary, for a vodka brand with a positive initial brand image, launching a line extension with perceived high quality led to a positive change in the brand image. (2) For vodka brands, a vertical line extension recognized as having high authenticity provokes a transfer of attributes from the extended product to the brand. (3) Among Keller’s (1993) dimensions of brand image, non-product related attributes and especially packaging are the one that are the most influenced by line extensions of vodka brands.